Peran Forum Koordinasi Pimpinan Daerah dalam Penyelenggaraan Otonomi Khusus di Provinsi DKI Jakarta - Andi Azikin (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2018)
The role of the Regional Leadership Coordination Forum (Forkopimda), so far has been more of a coordination forum that discussed problems in the region. The discussion was carried out in a form of meetings that were usually held in the local government office. The problems discussed are usually around the development of the last situation that occurred in the region. Other discussions usually depend on the theme or material of the discussion delivered by the Regional Head, which is then asked for advice from other Forkopinda members. In its development, it turned out that in addition to forums that were coordinating and discussing, it turned out that there were several activities in the field involving Forkopinda elements other than the Regional Head, in the form of handling social problems and natural disasters that were handled directly by TNI agencies and Polri agencies, even other institutions. who may not belong to Forkopinda.In addition to that role, Forkopinda, often also plays a role in the issue of public order, handling social conflicts, drug problems, population problems and family planning and foreign supervision problems.All of these problems require cross-sectoral coordination or coordination between vertical agencies in the region.